TMIC-15. HYPERACTIVATING THE HIPPO PATHWAY EFFECTOR TAZ DIFFERENTIALLY DISTORTS THE TUMOR MICROENVIRONMENT, PROMOTES TUMOR-ASSOCIATED NEUTROPHIL INFILTRATION, AND PHENOCOPIES MESENCHYMAL-GLIOBLASTOMA. (11th November 2019) - Yee, Patricia; Wei, Yiju; Liu, Zhijun; Guo, Hui; Manjibhai Vekariya, Umeshkumar; Anderson, Benjamin; Li, Wei
Abstract: Glioblastoma (GBM), the deadliest and most common adult brain malignancy, is molecularly and clinically heterogeneous. The most common subtype (both primary and recurrent), mesenchymal (MES)-GBM, has the worst prognosis and highest treatment resistance. MES-GBM exhibits hyperactive transcriptional coactivator with PDZ-binding motif ( TAZ ), a Hippo tumor suppressive pathway effector whose expression in GBMs predicts short survival. Yet, how Hippo-TAZ dysregulation might drive GBM MES transition remains elusive, precluding subtype-specific treatments. Tumor evolution requires signaling dysregulation and co-opting the tumor microenvironment (TME). Understanding GBM heterogeneity was recently complicated by the notion that subtypes vary in TME immune composition. The MES-GBM TME is differentially-distorted in silico, with more tumor-associated macrophages/microglia (TAMs) and neutrophils (TANs). Yet, how TAZ hyperactivity, MES transition, and GBM TME distortion interrelate and impact tumor progression remains unknown. We suspected that TME distortion facilitates immune evasion, MES transition, and tumor progression, worsening treatment responses. To test this, we devised an orthotopic xenograft mouse model phenotypically and histopathologically recapitulating human MES-GBM by expressing constitutively-active TAZ (TAZ 4SA ) in human GBM cells lacking MES signatures (GBM 4SA ). GBM 4SA mice lived significantly shorter compared to mice with GBM expressing vector (GBM vector ) or mutant TAZ unable to bind its effector, TEAD (GBM 4SA-S51A ). Moreover, more myeloid cells infiltrate the GBM 4SA TME than the GBM vector or GBM 4SA-S51A TMEs. While most myeloid cells infiltrating the GBM vector and GBM 4SA-S51A TMEs were TAMs, most infiltrating the GBM 4SA TME were TANs, suggesting TAZ hyperactivation differentially distorts the TME. Next, to delineate the roles of TANs in GBM 4SA tumor progression, mice were depleted of neutrophils by administering Ly6G antibody. Serial blood smears and flow cytometry revealed effective depletion was achieved. We are currently investigating the impact of systemic neutrophil depletion on GBM mesenchymal transition and tumor progression in hopes of informing future GBM clinical management and novel TME-targeted immunotherapies.